Brain regions related to fear extinction in obsessive-compulsive disorder and its relation to exposure therapy outcome: a morphometric study. Issue 4 (18th June 2013) - Fullana, M. A.; Cardoner, N.; Alonso, P.; Subirà, M.; López-Solà, C.; Pujol, J.; Segalàs, C.; Real, E.; Bossa, M.; Zacur, E.; Martínez-Zalacaín, I.; Bulbena, A.; et al.
Abstract : Background: The size of particular sub-regions within the ventromedial prefrontal cortex (vmPFC) has been associated with fear extinction in humans. Exposure therapy is a form of extinction learning widely used in the treatment of obsessive-compulsive disorder (OCD). Here we investigated the relationship between morphometric measurements of different sub-regions of the vmPFC and exposure therapy outcome in OCD. Method: A total of 74 OCD patients and 86 healthy controls underwent magnetic resonance imaging (MRI). Cortical thickness and volumetric measurements were obtained for the rostral anterior cingulate cortex (rACC), the medial orbital frontal cortex and the subcallosal cortex. After MRI acquisition, patients were enrolled in an exposure therapy protocol, and we assessed the relationship between MRI-derived measurements and treatment outcome. Baseline between-group differences for such measurements were also assessed. Results: Compared with healthy controls, OCD patients showed a thinner left rACC ( p = 0.008). Also, left rACC thickness was inversely associated with exposure therapy outcome ( r – 0.32, p = 0.008), and this region was significantly thinner in OCD patients who responded to exposure therapy than in those who did not ( p = 0.006). Analyses based on regional volumetry did not yield any significant results. Conclusions: OCD patients showed cortical thickness reductions in the left rACC, and these alterations were related to exposure therapy outcome. The precise characterization of neuroimaging predictors of treatment response derived from the study of the brain areas involved in fear extinction may optimize exposure therapy planning in OCD and other anxiety disorders.